ANALYSIS OF THE COGNITIVE AND MOTOR TEST OF THE TENNIS IN ADOLESCENTS OF PUBLIC SCHOOLS (Fiep Bulletin - online, 2014)
Introduction: the sport pedagogy has presented significant scientific approaches for the humanity and the court tennis under that prism has the obligation of giving its contribution in the school dimension. Objective: to analyze the experience in the modality and in the initial phase of cognitive and motor levels in adolescents of municipal public schools of the area west of Rio de Janeiro. Methodology: a field study with almost experimental characteristics was conducted in interpretative form, taking as starting point a sample constituted by 32 students in the age group from 13 to 16 years old of both sexes. Procedures: a questionnaire in which the students answered to 11 questions (in the yes or no format) pertaining to their sportive experience was used. Also a cognitive test (NUNES, 2004); with 5 specific questions regarding the 6 basic phases of one of the blows of the tennis; was answered (in the right or wrong format) individually by each student according to his comprehension of the subject. Furthermore, a motor test (HENSLEY, 1989), which consisted of the individual executing 10 tennis blows, the first 3 for adaptation and remaining 7 for validation, was conducted. Three specialists analyzed their motor proficiency. Results: in the sportive experience 68,75% of the sample had the same knowledge and of the idol through the media; in the cognitive test 62,50% of the sample answered in a correct form the specific subjects; and in the motor test 51,04% of the sample were classified as being at the moment proficiently weak. Conclusion: there was a significant influence of the media in what refers to the knowledge of the sport and of the idol, demonstrating that it is an important manner of diffusion of the sport; in the cognitive test the index of correct answers were considered high for their school level; and the motor test the results obtained were completely normal; thus if we implement the practice of this sport good results can be obtained.
Keywords: Tennis; adolescent; experience; cognitive; motor